Structural and Functional Analyses of the Transcription Repressor DgoR From Escherichia coli Reveal a Divalent Metal-Containing D-Galactonate Binding Pocket - Lin, Zhaozhu; Sun, Yi; Liu, Yu; Tong, Shujuan; Shang, Zhuo; Cai, Yuanheng; Lin, Wei (Frontiers in Microbiology, 2020)
The transcription repressor of D-galactonate metabolism, DgoR, from Escherichia coli belongs to the FadR family of the GntR superfamily. In the presence of D-galactonate, DgoR binds to two inverted repeats overlapping the dgo cis-acting promoter repressing the expression of genes involved in D-galactonate metabolism. To further understand the structural and molecular details of ligand and effector interactions between D-galactonate and this FadR family member, herein we solved the crystal structure of C-terminal domain of DgoR (DgoR_C), which revealed a unique divalent metal-containing substrate binding pocket. The metal ion is required for D-galactonate binding, as evidenced by the dramatically decreased affinity between D-galactonate and DgoR in the presence of EDTA, which can be reverted by the addition of Zn2+, Mg2+ and Ca2+. The key amino acid residues involved in the interactions between D-galactonate and DgoR were revealed by molecular docking studies and further validated with biochemical studies by site-directed mutagenesis. It was found that changes to alanine in residues R102, W181, T191, and R224 resulted in significantly decreased binding affinities for D-galactonate, as determined by EMSA and MST assays. These results suggest that the molecular modifications induced by a D-galactonate and a metal binding in the DgoR are required for DNA binding activity and consequently, transcriptional inhibition.